2018
DOI: 10.3892/ijo.2018.4552
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2R-mediated inflammasome activation is involved in tumor progression in breast cancer cells and in radiotherapy-resistant breast cancer

Abstract: In the tumor microenvironment, extracellular nucleotides are released and accumulate, and can activate the P2Y2 receptor (P2Y2R), which regulates various responses in tumor cells, resulting in tumor progression and metastasis. Moreover, the inflammasome has recently been reported to be associated with tumor progression. However, the role of P2Y2R in inflammasome activation in breast cancer cells is not yet well defined. Therefore, in this study, we investigated the role of P2Y2R in inflammasome-mediated tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 72 publications
(83 reference statements)
2
52
0
Order By: Relevance
“…However, P2Y 2 R has also been shown to be involved in pro-inflammatory responses [35,36]. Recently, it has been described that P2Y 2 R is required to induce IL-1β production in irradiated tumor cells by a pannexin-1-dependent mechanism [37], although the downstream P2Y 2 R signaling is unknown, it would suggest a physiological context in which macrophages would show a pro-inflammatory response as indicated in this manuscript. P2Y 2 R, as many G protein-coupled receptors, signals through PI3K, PLC activation and a subsequent intracellular calcium release [14], although the exact mechanism remains unclear [38,39].…”
Section: Discussionmentioning
confidence: 74%
“…However, P2Y 2 R has also been shown to be involved in pro-inflammatory responses [35,36]. Recently, it has been described that P2Y 2 R is required to induce IL-1β production in irradiated tumor cells by a pannexin-1-dependent mechanism [37], although the downstream P2Y 2 R signaling is unknown, it would suggest a physiological context in which macrophages would show a pro-inflammatory response as indicated in this manuscript. P2Y 2 R, as many G protein-coupled receptors, signals through PI3K, PLC activation and a subsequent intracellular calcium release [14], although the exact mechanism remains unclear [38,39].…”
Section: Discussionmentioning
confidence: 74%
“…P2Y 2 R expression is also significantly increased in tumor tissue and has a significant correlation only with Notch-4 of the cancer stem cell markers evaluated. In our previous study, we suggested that P2Y 2 R has an important role in tumor progression and metastasis in highly metastatic breast cancer cells, such as MDA-MB-231 and RT-R breast cancer cells (16)(17)(18)(19). In addition, Ko et al (19).…”
Section: Totalmentioning
confidence: 96%
“…Patients with HCC generally have a poor prognosis due to the highly invasive nature of the disease ( 2 ). A large number of studies have reported that the inactivation of tumor suppressor genes and the activation of oncogenes is responsible for the metastasis of HCC ( 3 - 5 ). However, the mechanisms underlying recurrence and metastasis in HCC have not yet been fully determined.…”
Section: Introductionmentioning
confidence: 99%